Is Surface Topography Useful in the Diagnosis of Scoliosis? Validation of the Biometrical Holistic of Human Body (BHOHB) - Angelo G. Aulisa; Diletta Bandinelli; Martina Marsiolo; Francesco Falciglia; Marco Giordano; Renato M. Toniolo (MDPI AG, 2023)
Background: The concern around repeated exposure to X-rays has been motivating doctors involved in scoliosis to seek alternative solutions. Surface topography (ST) analysis is a modern system that has been shown to have good results. The purpose of the study is to validate the new BHOHB hardware for the investigation of scoliosis in adolescents by comparing it to X-ray examinations and to assess the reliability of intraoperator and interoperator tests. Methods: Ninety-five patients were enrolled in our study. All the patients were analyzed via the BHOHB method 2 times by 2 independent physicians (t0) and for a second time 2 or 3 months later (t1). The Pearson correlation coefficient was used to evaluate the relationship between the measurements obtained by BHOHB and the gold standard. The intraclass correlation coefficient (ICC) was used to assess intra- and interoperator reliability. Statistical analysis was performed with the GraphPad Prism 8 software. Results: The correlations between the first and second operators in the measurements and between the BHOHB method and X-ray showed a very good to excellent r for both. A very good correlation was also confirmed for prominence measured by operators and by the BHOHB machine. Intra- and interoperator reliability was found to be very positive for both the first and the second physicians. Conclusions: We can state that ST can be useful for diagnosing and treating scoliosis. The recommendation is to use it primarily to evaluate the evolution of the curve, as in this mode, you can reduce the patient's exposure to X-rays. The results indicate that BHOHB measures are comparable to radiographs and not influenced by the operator.